Life and Technology An Inquiry Into and Beyond Simondon - Barthélémy, Jean-Hugues (After Simondon, 2015)
The philosophy of Gilbert Simondon has reinvigorated contemporary thinking about biological and technological beings. In this book, Jean-Hugues Barthélémy takes up Simondon's thought and shows how life and technology are connected by a transversal theme: individuation. In the first essay, Barthélémy delivers a contemporary interpretation of Simondon's concept of ontogenesis against the backdrop of biology and cybernetics. In the second essay, he extends his reflections to propose a non-anthropological understanding of technology, and so sets up a confrontation with the work of Martin Heidegger.